Assessing Sustainable Value Creation in Social Enterprises - Go, George Isaac Y. (Archīum Ateneo, 2022)
This research explored how ten social enterprises (SEs) in the Philippines create environmental, economic, and social value in the short and long term. This analysis of sustainable value creation (SVC) was the basis for the development of an assessment tool using the sustainable value framework of Hart and Milstein (2003). The resulting assessment tool, referred to as the SVC-SE Assessment Tool, allows SEs to do a rapid assessment on how they generate environmental, economic, and social effectiveness, efficiency and resilience. A portfolio balance indicates if the SE is creating sustainable value and the resulting scores per aspect and quadrant can help the SE get a sense of performance in the different aspects of SVC. The tool that can give a quick overview of the current SVC of the SE and can also provide assistance in planning for future activities.